PBL Student Worksheet with PhET Simulations: Improving Cognitive Learning Outcomes on Simple Machines - Widyaputri, Mutya Ardha; Wilujeng, Insih; Rahmawati, Laifa (Department of Physics Education, Universitas Mataram, 2025)
This study aims to analyze the cognitive learning outcomes of students before and after using PBL student worksheets assisted by PhET Simulations on simple aircraft material. This study used a quasi-experimental method with a one-group pretest-posttest design. The research subjects were 32 students of class VIII H at SMPN X Yogyakarta in the odd semester of the 2023/2024 school year which was determined by purposive sampling technique. The instrument used was a multiple choice test of 15 items that measured cognitive learning outcomes based on Bloom's cognitive taxonomy levels C2, C3, C4. The results showed a significant increase in the cognitive learning outcomes of students before and after using PBL student worksheets assisted by PhET Simulations on simple aircraft material. The pretest average score of 61.97 increased to 84.41 on the posttest, exceeding the minimum completeness criteria. The normality test shows that the data is normally distributed. The paired sample t-test produced a significance value of 0.000 (p < 0.05), which showed a significant difference between the pretest and posttest. The effect size value of 1.73 is in the large category, indicating a strong influence of the treatment on students' cognitive learning outcomes